PENGARUH MODEL PEMBELAJARAN OPEN ENDED TERHADAP HASIL BELAJAR MATERI PENJUMLAHAN DI KELAS I SD NEGERI 101735 SEI SEMAYANG T.A 2021/2022 - Eden Seftika Br Sitepu; Taruli Marito Silalahi (Program Studi Pendidikan Guru Pendidikan Anak Usia Dini (PGPAUD), 2022)
The purpose of this study is to determine the influence of open ended learning model on Student’s mathematics learning outcomes of addition material in class I SDN 101735 Sei Semayang. This research is experimental research with Quantitative approach with One Group Pre Test Post Test Design. The population in this study were first grade students of SDN 101735 Sei Semayang. Sampling technique is Total Sampling. The sample of this study were 28 students. The data collection technique were carried out throught test, observation and documentation. Data was analyzed by t test. Based on the t test result, it found that sign.(2 – tailed) for Pre - test and Post - test was 0.000 < 0.05, It Means that hypothesis Ho is rejected and Ha is accepted. It can be concluded that there is an influence of open ended learning model on Student’s mathematics learning outcomes of addition material in class I SDN 101735 Sei Semayang in Academic Year of 2021/2022